Pemanfaatan Website sebagai Alat Digital Marketing untuk UMKM Laundry Putri di Kota Padang - Asyih Zatayu; Faisal; Fausiah Yasmin; Sularno; Novadilastri (CV. ITTC INDONESIA, 2024)
This research examines the use of blogs as a digital marketing strategy for Putri Laundry MSMEs in Padang City. Using a descriptive qualitative approach, this study involves direct observation and in-depth interviews to analyze the implementation of blogs in increasing online visibility, expanding market reach, and increasing interaction with customers. The results show that the owner of Putri Laundry is interested in utilizing blogs as a platform to provide service information, publish promotions, and share clothing care tips. Blog development process, from design to implementation.